Immunohistochemical expression of Aromatase in malignant breast tumours - Abdul-Jabbar, Rawaa Abdul-Ameer (Iraqi Journal of Cancer and Medical Genetics, 2016)
Twenty tumour biopsies of Iraqi breast cancer female patients were examined for immunohistochemical (IHC) expression of aromatase. The expression was correlated with age and histopathological type, grade and clinical staging of tumour. Results revealed that out of the 20 investigated cases, 75.0% showed positive IHC expression of aromatase, which was distributed as 35.0% for score 2+ and 40.0% for score 3+. The remaining five negative cases (25.0%) were observed to have the lowest age mean (38.6 ± 4.4 years), which was significantly different from the recorded age mean in patients with the score 2+ (53.6 ± 3.2 years; p = 0.008) or 3+ (49.4 ± 2.8; p = 0.04), but no significant difference was observed between age means of positive cases. A histpathological examination of tumours revealed that they were invasive ductal carcinoma (IDC) but of two types: tubular IDC (5 cases; 25.0%) and 15 cases (75.0%) were defined as not otherwise specified (IDC-NOS). In tubular IDC, most of cases (80.0%) had 3+ score, while in IDC-NOS, it was 26.7%. Such difference was significant (p = 0.023). Distributing patients by grade and stage of tumours revealed no significant difference in IHC scoring of aromatase or age. It is possible to conclude that positive IHC expression of aromatase is tended to occur in older ages (around 50 years) of breast cancer patients.